El pensamiento político en la modernidad - González Hernández, Bryan (2010)
In this article I examine the emergence of modern political thought and the unfulfilled promises that characterized modernity. If the Peace of Westphalia (1648) marks the beginning of modern political thought, the article explores the possibility of a «new peace of Westphalia» to confront the crisis of the paradigm of Modernity.